Le paysage fluvial et irrigué de Sarazm dans la moyenne vallée du Zeravchan, Tadjikistan, Asie centrale - Lucie Cez (Projets de Paysage)
The geoarchaeological study of the river landscape of the Zeravchan Valley highlights the role of water as a morphogenic agent and the importance of factors controlling river dynamics according to different timelines. This landscape is also the result of interactions between the dynamics of this semi-arid and tectonically active area and the riparian societies that have developed there since the protohistoric era. This methodological approach is based on a multilevel study of the archives of the river landscape and the remains of hydraulic structures. The archaeological data are supplemented by a geomorphological study, Optically Stimulated Thermoluminescence (OSL) dating and micromorphological analysis of the sedimentary backfill of a canal which was in use in the 3rd millennium BE. This study shows that socio-environmental interactions, related to human settlement and water management in a challenging environment, contribute to the creation of such a water landscape over very short periods of time as well as over several millennia.